Winter2005 Final with solutions

Winter2005 Final with solutions - MATH 135 Final Exam...

Info iconThis preview shows pages 1–5. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MATH 135 Final Exam Solutions Page 1 of 11 Winter 2005 1. (a) Determine the complete solution to the linear Diophantine equation [6] 391 x + 253 y = 2760 . Solution: The Extended Euclidean Algorithm gives 1 391 1 253 1 1-1 138 1-1 2 115 1 2-3 23 5-11 17 Thus, 391(2) + 253( 3) = 23 and gcd(391 , 253) = 23. Further, 391(240) + 253( 360) = 2760 . The complete solution is x = 240 + 11 n y = 360 17 n n Z . (b) Suppose that the complete solution to a linear Diophantine equation is given by [4] j = 23 3 n k = 521 + 50 n n Z . List all positive solutions. Solution: j k 23 3 n 521 + 50 n 3 n 23 50 n 521 n 7 . 6 n 10 . 42 Thus 7 . 6 n 10 . 42. Valid values of n are -10, 9, -8. The positive solutions are: n j k-10 7 21-9 4 71-8 1 121 MATH 135 Final Exam Solutions Page 2 of 11 Winter 2005 2. (a) Prove that if a, b, c Z with c | ab and gcd( a, c ) = 1 then c | b . [4] Solution: Since gcd( a, c ) = 1, x, y Z with ax + cy = 1. Multiplying by b gives axb + cby = b . Since c | ab and | cby , thus c | b . (b) If z = x + iy is a complex number in standard form and z negationslash = 0, give an expression for z- 1 [3] and prove that z z- 1 = 1 . Solution: z- 1 = x- iy x 2 + y 2 . z z- 1 = ( x + iy )( x iy x 2 + y 2 ) = x 2 i 2 y 2 x 2 + y 2 = 1 MATH 135 Final Exam Solutions Page 3 of 11 Winter 2005 3. Prove that 1 3 + 5 7 + ... + ( 1) n- 1 (2 n 1) = ( 1) n- 1 n n P . [6] Solution: Proof by mathematical induction. When n = 1, 1 = ( 1) 1- 1 1. Suppose that 1 3 + 5 7 + ... + ( 1) k- 1 (2 k 1) = ( 1) k- 1 ( k ). Consider 1 3 + 5 7 + ... + ( 1) k- 1 (2 k 1) + ( 1) k (2 k + 1) = ( 1) k- 1 ( k ) + ( 1) k (2 k + 1) by the induction hypothesis = ( 1) k- 1 ( k 2 k 1) = ( 1) k- 1 ( k 1) = ( 1) k ( k + 1) By mathematical induction, 1 3 + 5 7 + ... + ( 1) n- 1 (2 n 1) =) 1) n- 1 n n P . MATH 135 Final Exam Solutions Page 4 of 11 Winter 2005 4. (a) State Fermats Little Theorem. [3] Solution: If p is a prime and p negationslash | a then a p- 1 1 (mod p ). (b) Find all solutions to 14 x 11 + 33 x 8 + 32 0 (mod 77). [6] Solution: By the Chinese Remainder Theorem and Fermats Little Theorem, this is equivalent to the following congruences: braceleftBigg 14 x 11 + 33 x 8 + 32 0 (mod 7) 14 x 11 + 33 x 8 + 32 0 (mod 11) OR braceleftBigg 5 x 8 + 4 0 (mod 7) 3 x 11 1 (mod 11) OR braceleftBigg 5 x 2 3 (mod 7) (since x 7 x (mod 7)) 3 x 1 (mod 11) (since x 11 x (mod 11))...
View Full Document

Page1 / 11

Winter2005 Final with solutions - MATH 135 Final Exam...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online